2020
DOI: 10.3389/fmicb.2020.01196
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effects of Volatiles Produced by Bacillus subtilis Against Alternaria solani in Potato

Abstract: Antifungal activities of plant-beneficial Bacillus have been widely studied in recent years. Numerous studies have studied the antifungal mechanisms of soluble nonvolatile bioactive compounds such as lipopeptides and proteins produced by Bacillus against soil-borne diseases. However, the antagonistic mechanisms of volatile organic compounds (VOCs) from Bacillus against airborne phytopathogens are still largely unknown, and the function of Alternaria solani pathogenic genes has not been well identified. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 44 publications
1
60
2
1
Order By: Relevance
“…In contrast, a volatile organic compound (VOC) assay revealed that none of the isolated exhibited inhibitory activity against any of the tested fungi. These results conflict with previous studies in which VOC inhibitory activity by Bacillus strains against Aspergillus , Fusarium , and Alternaria species has been reported [ 40 , 41 , 42 ].…”
Section: Resultscontrasting
confidence: 99%
“…In contrast, a volatile organic compound (VOC) assay revealed that none of the isolated exhibited inhibitory activity against any of the tested fungi. These results conflict with previous studies in which VOC inhibitory activity by Bacillus strains against Aspergillus , Fusarium , and Alternaria species has been reported [ 40 , 41 , 42 ].…”
Section: Resultscontrasting
confidence: 99%
“…These micro-organisms include bacteria such as Bacillus sp. (Zheng et al 2013;Morita et al 2019;Zhang et al 2020), Pseudomonas sp. (Elkahoui et al 2015) and Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 3 lipopeptides from B. subtilis were described to be effective against Venturia inaequalis, fungi causing apple scab [30]. Zhang et al also proved the efficacy of volatile oil compounds produced by Bacillus strain ZD01, against A. solani, a fungal pathogen causing diseases of potato [31]. Moreover, B. subtilis subsp.…”
Section: Discussionmentioning
confidence: 99%